Evaluating Urban Heat Island Effects in the Southwestern Plateau of China: A Comparative Analysis of Nine Estimation Methods - Ziyang Ma; Huyan Fu; Jianghai Wen; Zhiru Chen (Land)
Surface urban heat island intensity (SUHII) is a critical indicator of the urban heat island (UHI) effect. However, discrepancies in estimation methods may introduce uncertainty in SUHII values. While previous studies have examined the responses of SUHII to different methods at large scales, further analysis is needed for plateau cities in southwestern China, which have complex geographical features. This study investigates the spatiotemporal patterns and influencing factors of SUHII in 200 plateau cities across southwestern China via nine estimation methods that incorporate rural ranges and elevation-based conditions. The results show that: (1) The annual average daytime and nighttime SUHII for these cities were 0.97 ± 0.78 °C (mean ± std) and 0.21 ± 0.87 °C, respectively. For 22% of the cities during the day and 26% at night, the choice of different SUHII estimation methods resulted in the transformation between a surface urban heat island (SUHI) and a surface urban cold island (SUCI) due to the exclusion of rural pixels more than ±50 m from the median urban elevation. Compared with other regions, high-altitude plateau cities exhibited a slightly lower daytime SUHII but a significantly higher nighttime SUHII because of the lower atmospheric pressure in plateau areas, which limits the conduction and retention of heat. Consequently, heat dissipates more quickly at night, increasing SUHII values. (2) The mean ΔSUHIIAD (absolute difference in SUHII values across methods) was 0.51 ± 0.01 °C during the day and 0.44 ± 0.02 °C at night. (3) In high-altitude plateau cities, for all methods, the correlation of the SUHII with influencing factors was stronger, highlighting their sensitivity to both environmental and anthropogenic influences. These results enhance our understanding of plateau UHI dynamics and highlight the importance of considering appropriate rural definitions for cities with varying geographical characteristics.